Oribatid mites (Acari: Oribatida) from Austrocedrus chilensis and Nothofagus forests of Northwestern Patagonia (Argentina) - Kun, Marcelo Eduardo; Martínez, Pablo Antonio; Gonzalez, Alda
Forest sites in Northwestern Argentinean Patagonia were surveyed to determine the oribatid mite fauna. A taxonomic inventory of oribatid mites was carried out in Northwestern Argentinean Patagonia to establish the taxonomic diversity, for increasing the knowledge of their distribution, detecting new species and assessing environmental effects on the oribatid mite community. Eleven sampling sites in nearly pure forests of Austrocedrus chilensis, Nothofagus dombeyi, Nothofagus antarctica were selected as these are among the most recurrent arboreal species found in this region. Samples of leaf litter, soil and pitfall traps contents were taken from each forest. Fifty-five oribatid species, belonging to 46 genera in 28 families, were found. Nine species are new records for Argentina and one for continental Argentina. Thirty-two species were recorded in A. chilensis forests, 35 in N. dombeyi forests and 20 in N. antarctica forests. Fifty species were found in leaf litter, 35 in soil and eight in pitfall traps. Fourteen species were recorded exclusively in leaf litter, one in soil and four in pitfall traps. A high level of endemism is confirmed as nearly 62 % of collected species have previously been found only in Southern Andes supporting the existence of an associated autochthonous oribatid fauna Fil: Kun, Marcelo Eduardo. Universidad Nacional del Comahue. Centro Regional Universidad Bariloche. Departamento de Zoología; Argentina Fil: Martínez, Pablo Antonio. Universidad Nacional de Mar del Plata. Facultad de Ciencias Exactas y Naturales. Departamento de Biología; Argentina Fil: Gonzalez, Alda. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Estudios Parasitológicos y de Vectores. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Centro de Estudios Parasitológicos y de Vectores; Argentina